A review of data sources for electric vehicle integration studies. (November 2021) - Calearo, Lisa; Marinelli, Mattia; Ziras, Charalampos
Abstract: The sales of electric vehicles (EVs) are rapidly increasing and their integration in the power system is becoming a crucial issue. However, there is a scarcity of necessary data to derive charging profiles and analyze their impact on the power system. The purpose of this manuscript is to provide a comprehensive review of published data sources that can be useful for EV studies in the context of smart grids and power systems. The manuscript focuses on the last two decades of published data, as this is more complete and reliable in terms of user and vehicle behavior. Data sources are categorized into three classes: surveys, internal combustion engine vehicles and EVs trials, and charger trials. Data from the different sources are summarized, including information regarding how and what kind of data has been collected and their availability. Based on the reviewed sources, five parameters are identified as essential to derive charging profiles: battery capacity, charging power, plug-in state of charge, plug-in/out time and charged energy. In order to observe individual behavior it is important to consider sets of charging sessions per charger, otherwise important correlations may be neglected. Depending on the source and data availability, in many cases this is not possible. To this end, this manuscript discusses how to use data from various sources to complement missing information and concludes with guidelines and limitations about data usage in EV studies. Highlights: Review of data sources for EV charging and driving studies. Definition of ideal dataset of conducting EV studies. Guidelines and limitations for data usage in EV studies.